2022
DOI: 10.14715/cmb/2022.68.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of miRNA-146a-mediated TLR4 Signal Pathway on the Pain of Lumbar Disc Herniation

Abstract: The current experiment was carried out to explore the effect of the miR-146a-mediated TLR4 signaling pathway on the lumbar disc herniation pains. For this aim, a total of 32 rats were divided randomly into 4 groups – the blank group (Group C), Model group (M), miR-146a overexpression group (agomiR-146a group) and negative control group (NC group), with 8 rats in each group. Rats in Group M were prepared for the construction of lumbar disc herniation models, while those in the agomiR-146a group or NC group, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…28 Animal models of disc degeneration have also shown an association between increased TLR4 expression and pain, while inhibition of TLR4 decreased pain and pro-inflammatory cytokine production. [34][35][36] However, the extent to which inflammatory signaling resulting from TLR activation causes pain behavior requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Animal models of disc degeneration have also shown an association between increased TLR4 expression and pain, while inhibition of TLR4 decreased pain and pro-inflammatory cytokine production. [34][35][36] However, the extent to which inflammatory signaling resulting from TLR activation causes pain behavior requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Further, injection of LPS directly into the nucleus pulposus (NP) space of rat caudal IVDs has caused moderate degenerative changes in the IVD, with increases in tissue levels of IL‐1β, TNFα, HMGB1, and macrophage migration inhibitory factor (MIF) 28 . Animal models of disc degeneration have also shown an association between increased TLR4 expression and pain, while inhibition of TLR4 decreased pain and pro‐inflammatory cytokine production 34–36 . However, the extent to which inflammatory signaling resulting from TLR activation causes pain behavior requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the influences of circulating miR-342 on radiation-induced injury, the radiation-induced decrease in the level of miR-342 was reversed by tail vein injection with one kind of miR-342 mimetics (AgomiR-342). AgomiRNA is widely used to study the function of miRNAs in vivo ( 34 , 35 ). We found that injection with 5 nmol AgomiR-342 could upregulate the level of miR-342 in blood more than 8 times (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…(Gada et al, 2021). Jing et al (2022) found that upregulating the expression of miR-146a in rats with LDH could reduce the activity of the TLR4 signaling pathway, thus relieving pain. Through highthroughput sequencing technology, Yao et al (2022b) found that there were 19 expressed miRNAs that were related to inflammation in chronic compression of dorsal root ganglia (CCD) rats treated with pressing and kneading "Weizhong" (BL40) compared to CCD model rats.…”
Section: Tuina Exerts Analgesic Effects By Suppressing Peripheral Inf...mentioning
confidence: 99%